RI 7469 Waterflooding Of Oilfields In Wyoming To 1968 - Paul Biggs (The National Institute for Occupational Safety and Health (NIOSH), 1970)
This Bureau of Mines report provides information on 138 waterflood projects in Wyoming. Injection was in 25 producing zones and 65 fields. Specific data presented include field location, discovery and development, water supply and injection, oil and water production, estimates of oil in place, and oil recoveries by primary and secondary methods. The 138 projects studied will, if successful, recover about 800 million barrels of secondary oil. Almost all of the injection water is from deep water wells.